OPTIMALISASI LEMBAGA AMIL ZAKAT UNTUK PENYALURAN ZAKAT BAGI GOLONGAN GHARIMIN - Sucita Fitri, Annisa (UI Scholars Hub, 2021)
Gharimin or people who carry debts are one of eight groups who are entitled to receive zakat distribution (asnaf). Gharimin with certain criteria, in principle, will be helped to pay off their obligations through the receipt of zakat. However, there are many gharimin who have to get back into new debt or loans, either conventional or online loans, which threaten them to pay big interest. It was later discovered that zakat receipts by the Amil Zakat Institution (LAZ), especially those that would be distributed to the mustahik of the Gharimin group, were still not maximized, so high-interest loans were still the main solution for these debtors. This study seeks to provide an overview of the conditions of zakat distribution, especially for Gharimin related to the condition of the Amil Zakat Institution as one of the main zakat collection institutions in Indonesia, and how the positive implications that can arise if the collection and distribution of zakat have been carried out optimally. This research is considered important because as Muslims, the principle of helping and easing the burden of brothers and sisters in faith is a must, coupled with the obligation to pay zakat, making this research relevant to be carried out.